Fihrist-i kutub-i ʻArabī, Fārsī va Urdū maḵẖzūnah-yi Kutub Ḵẖānah-yi Āṣafiyah Sarkār-i ʻĀlī : az ibtidā-yi qayām-i kutub ḵẖānah 1300 F. tā 1321 F. mut̤ābiq 1330 H. - Osman Ali, Nizam of Hyderabad, 1886-1967 (SAMP early 20th-century Indian books project, 1928)
Catalogs of books preserved at Kutub Ḵẖānah-yi Āṣafiyah Sarkār-i ʻĀlī, Hyderabad, India.